Implementation of Women's Education in the Green Aksara Community in Dengok Village, Playen District, Gunung Kidul Regency for Sustainable Development - Raudya Setya Wismoko Putri; Liliek Pratiwi; Gita Milenia Setya Wismoko Putri (Jurnal Pengabdian West Science, 2024)
Abstract: This research aims to 1) describe the implementation of women's education for sustainable development by tutors and technical resource persons at the Green Aksara Association, 2) describe the supporting and inhibiting factors in the implementation of women's education for sustainable development. This research is descriptive research with a qualitative approach. The subjects of this research are institutional managers, technical resource persons, accompanying tutors and students who study. Data collection used participatory observation methods, in-depth interviews, and documentation. The researcher is the main research instrument with the help of observation guidelines, interview guidelines and documentation guidelines. The data analysis techniques used are data display, data reduction and conclusion drawing. Triangulation is carried out to explain the validity of the data using source triangulation. The results of the research show 1) the implementation of women's education for sustainable development in the green script community delivers environmentally friendly literacy and skills material, applied with participatory learning principles which appear in learning materials, learning preparation, preparation and learning stages, learning media and learning evaluation. 2) supporting factors for the implementation of women's education include the commitment of institutional management, support and participation from partners, application of participatory learning principles, and easy access to learning facilities. Meanwhile, the obstacles are increasing the time to repeat material for the elderly, learning time at the same time as agricultural activities, the educational skills possessed by the resource persons are still lacking.